Effect of Merit System and Work Achievement on Employee Competence at PT Purnatarum Murni Rahayu Bandung - Hari Imbrani; Iwan Setiawan (Quantitative Economics and Management Studies, 2023)
Purnatarum Murni Rahayu is engaged in providing Liquid Petroleum Gas (LPG) services for the Greater Bandung area, as a company that functions as storage, the employees are required to have good competence, this is related to employee performance and employee recruitment planning. This study aims to determine whether the merit system variable has a significant effect on employee competence and whether work performance has a significant effect on employee competence. The research method used is descriptive, verification, namely by describing each variable and testing the three variables with a quantitative (statistical) approach which is then analyzed and compared with existing theories and problems to conclude. Simultaneously the magnitude of the effect of the merit system and work performance is 67.4% on competence while other factors are not examined (epsilon) but affect competence at 33.6%. The results of the study which are based on the partial hypothesis state that the merit system and work performance variables can be detected from the magnitude of the influence of each factor consisting of the merit system factor (X1of32.1%, work performance factor (X235) of,5%, to the competence of employees at PT. Purnatarum Murni Rahayu. This study concludes that the merit system has an effect on employee competence and work performance has a more dominant influence on employee competence than the merit system